Diagnosis and treatment of early eosinophilic fasciitis: a case report - Jinlu Ma; Yunping Cai; Han Shao; Jingjing Dou; Yusheng Yang; Xiaoli Fan; Cui Lu (Journal of Medical Case Reports)
Abstract Background Eosinophilic fasciitis is an infrequent connective tissue disorder that often delays treatment owing to misdiagnosis or omission. In advanced stages, severe skin sclerosis can lead to joint contracture and tendon retraction, which can severely affect the quality of life. Therefore, it is important to make a clear diagnosis and intervene in the early stages of the disease. Case presentation We report a case of a 52-year-old Chinese patient with marked symmetric swelling of her extremities, especially forearms and calves, sclerosis of the subcutaneous tissue, limited joint mobility, and whose serologic markers showed markedly elevated serum eosinophils at the beginning of the consultation. The diagnosis of eosinophilic fasciitis was further clarified and treated after refinement of soft tissue magnetic resonance imaging and subcutaneous tissue biopsy, and the patient responded favorably to treatment with marked improvement in cutaneous sclerosis and the quality of life. Conclusion Enhanced magnetic resonance imaging and whole-layer biopsy plays a critical role in enabling early diagnosis of eosinophilic fasciitis, while early treatment with a combination of glucocorticoids and methotrexate significantly improves the clinical symptoms of the disease.